Archaeology, Heritage and Ethics in the Western Wall Plaza, Jerusalem Darkness at the End of the Tunnel - Kletter, Raz (Taylor & Francis, 2019)
This volume is a critical study of recent archaeology in the Western Wall Plaza area, Jerusalem. Considered one of the holiest places on Earth for Jews and Muslims, it is also a place of controversy, where the State marks 'our' remains for preservation and adoration and 'theirs' for silencing.